Enhancing healthcare professionals’ capacity in early detection of prostate cancer - Rahman, Eka Yudha; Panghiyangani, Roselina; Kania, Nia; Sutapa, Hendra; Yulizar, Deddy Rasyidan; Budiwinata, Winardi; Skripsiana, Nika Sterina; Rachman, M. Fathur; Fatharoni, Gusti Dicky; Fahdyanoor, Fahdyanoor (Universitas Muhammadiyah Magelang, 2025)
Prostate cancer is globally the second most common malignancy and the sixth leading cause of cancer-related death in men. The growing elderly population in Banjarbaru City, South Kalimantan, further elevates the risk of prostate cancer incidence in the region. Therefore, this community service initiative aimed to improve the knowledge and skills of healthcare professionals serving the elderly within the working area of the Banjarbaru City Health Office in early detection and prevention of prostate cancer. The activity was conducted as a comprehensive training involving 20 healthcare professionals, encompassing both theoretical and practical sessions. Training outcomes revealed a significant increase in participants' knowledge, evidenced by an average pre-test score of 55.91 which rose to an average post-test score of 84.35. Additionally, there was a noticeable improvement in healthcare professionals' skills in performing early detection and preventive measures for prostate cancer. Overall, this training successfully enhanced the capacity of healthcare professionals in Banjarbaru City in the early management of prostate cancer.